Corporeïtat, conflicte i abjecció en Les mans de la deixebla d'Anna Moner. - MIRA-NAVARRO, IRENE (Scripta, 2019)
The main aim of this article is to analyse the novel Les mans de la deixebla by Anna Moner (2011) both as a novel through gothic narration and the historical environment of the XVIII century, and as the exponent of the corporeality's representation. We study the mechanisms through which the author builds three complex characters that turn around the conflict generated by the abject nature of the main character's body (Kristeva 2006). From this point on, we look to explore how the deformed hands become into a symbol that connects with the gothic tradition (Cornich and Sedgwick 2017). In this novel, the hands also play the role of a disruptive agent of the main character's psychology. We will study the abjection process of the main character related to the rejection of the own body and, at the same time, to its instrumentalization as an agent capable of undermining the illustrated conception of science as a means of progress.